2021
DOI: 10.51253/pafmj.v71i5.5357
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Anti-Retroviral Therapy (Art) to Hiv Patients and Their Preventive Practices Against Covid-19 Pandemic - A Syndemic Perspective From a Hiv Center in Pakistan

Abstract: Objective: To see the implementation of designed strategy for uninterrupted supply of HIV treatment at time of COVID-19 Pandemic along with the knowledge and preventive practices regarding COVID-19 among HIV positive patients to have baseline data for future interventions to control HIV-COVID-19 syndemic. Study Design: Cross sectional study. Place and Duration of Study: HIV Center at Benazir Bhutto Shaheed Hospital, Karachi Pakistan, from Mar to May 2020. Methodology: 100 patients who visited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…A cross-sectional study from Pakistan involving 385 adolescents aimed to determine the incidence of eye strain from working on ICT devices and its association with time spent in front of ICT device screens. The research results showed that the most common symptoms were headache (47.3%), tired eyes (33.7%), blurred vision (25%), eyestrain (22.3%), irritated or painful eyes (15%), and dry eyes (9.6%) (21), indicating that eye fatigue was the only symptom consistent with the finding of our study, while all other symptoms were significantly more common among respondents from Pakistan.…”
Section: Khalaj Et Al Examined Vision Problems and Their Associationsupporting
confidence: 88%
“…A cross-sectional study from Pakistan involving 385 adolescents aimed to determine the incidence of eye strain from working on ICT devices and its association with time spent in front of ICT device screens. The research results showed that the most common symptoms were headache (47.3%), tired eyes (33.7%), blurred vision (25%), eyestrain (22.3%), irritated or painful eyes (15%), and dry eyes (9.6%) (21), indicating that eye fatigue was the only symptom consistent with the finding of our study, while all other symptoms were significantly more common among respondents from Pakistan.…”
Section: Khalaj Et Al Examined Vision Problems and Their Associationsupporting
confidence: 88%
“…One of these is eye strain, to which radiologists are more prone than physicians in other specialities. According to the American Optometric Association, the physical discomfort felt after continuous use of digital screens (computers and other electronic displays) is called digital eye strain (DES) or computer vision syndrome (CVS) 1 , 2 . Digital devices have become an essential part of our day-to-day lives and are used for various professional and other purposes 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%